The winding road to fair value accounting in China: a social movement analysis. Issue 4 (21st May 2018) - Bewley, Kathryn; Graham, Cameron; Peng, Songlan
Abstract : Purpose: The purpose of this paper is to examine China's stop-start adoption of fair value accounting (FVA) into its national accounting standards. The paper analyzes how FVA standards promoted by transnational organizations were eventually adopted in China despite its conservative accounting traditions. Design/methodology/approach: The study uses archival records and an analytic framework adapted from the studies of social movements to identify the institutional factors that differ between China' first unsuccessful attempt to adopt FVA and its second successful attempt. Findings: Shared interests of elite national and international groups, creation of social infrastructure, marshaling of key resources, and specific actions to frame FVA standards are found to be crucial factors supporting FVA reform in China. Practical implications: The study helps advance our understanding of dissemination of international accounting regulations in non-Western societies. The findings can help accounting standard setters to avoid costly failures. Originality/value: The study provides a structured analysis of the propagation of global accounting regulations. It exposes the factors in the failure and success of FVA adoption in China.